2018
DOI: 10.1155/2018/6297362
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intraoperative Dexamethasone and Ondansetron on Postoperative Nausea and Vomiting in Microvascular Decompression Surgery: A Randomized Controlled Study

Abstract: Background Postoperative nausea and vomiting (PONV) is a common problem and may lead to catastrophic complications, especially in neurosurgical cases. The aim of this study was to evaluate the effects of dexamethasone and ondansetron for preventing PONV in patients who underwent microvascular decompression (MVD) surgery. Methods A prospective, double-blinded, randomized control trial was conducted with 54 patients who underwent MVD. Patients were allocated into two groups. The study group (Gr. D) received intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 16 publications
3
10
0
Order By: Relevance
“…In the current study, approximately 40.0% patients experienced vomiting and 60.0% patients experienced nausea on POD 1 after MVD surgery, despite pre-emptive treatments to prevent PONV. This PONV rate observed in our study is similar to previous studies [ 3 5 ]. We also found that IOP reduction after MVD surgery is an independent risk factor for vomiting on POD 1.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the current study, approximately 40.0% patients experienced vomiting and 60.0% patients experienced nausea on POD 1 after MVD surgery, despite pre-emptive treatments to prevent PONV. This PONV rate observed in our study is similar to previous studies [ 3 5 ]. We also found that IOP reduction after MVD surgery is an independent risk factor for vomiting on POD 1.…”
Section: Discussionsupporting
confidence: 93%
“…Microvascular decompression (MVD) is the standard treatment for hyperactive dysfunctional cranial nerve syndromes (such as trigeminal neuralgia, hemifacial spasm, and glossopharyngeal neuralgia) in patients who do not respond to or tolerate pharmacological treatments [ 1 , 2 ]. A significant proportion of patients experience severe postoperative nausea and vomiting (PONV) in the first 24 h after surgery [ 3 5 ]. PONV increases complications (e.g., surgical site bleeding, electrolyte disturbance, dehydration, and aspiration) and delays postoperative recovery [ 2 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…This must be because of double antiemetic prophylaxis with Dexamethasone and Ondansteron, which we usually follow for our neurosurgical patients. The efficacy of regime is proven through various studies 12 and the results here is validating the same. HTN and desaturation were the most frequent cardiorespiratory events recorded in this study.…”
Section: Discussionsupporting
confidence: 70%
“…However, Kim et al 148 failed to find a difference 174 as well as in endoscopic adenoidectomy 175 and strabismus correction surgery 176 in children. Interestingly, there are reports that dexamethasone did not reduce PONV in patients undergoing surgery for facial fracture 177 , laparoscopic surgery for suspected appendicitis 178 , and microvascular decompression surgery of the trigeminal nerve root 179 . Singh et al 180 concluded that dexamethasone has equal antiemetic efficacy compared to 5-HT 3 receptor antagonists up to 24 hours after surgery.…”
Section: Tricyclic Antidepressantsmentioning
confidence: 99%
“…Dexamethasone antiemetic efficacy alone or in combination has been reported in patients undergoing laparoscopic cholecystectomy 153 164 , other abdominal laparoscopic procedures 150 , breast cancer surgery 165 , large and small bowel surgery 166 , total knee arthroplasty 167 , joint replacement surgery 168 , gynecological laparoscopic procedures 169 , 170 , cesarean delivery 171 , scoliosis correction surgery 172 , vitrectomy under local anesthesia 173 , and upper extremity surgery 174 as well as in endoscopic adenoidectomy 175 and strabismus correction surgery 176 in children. Interestingly, there are reports that dexamethasone did not reduce PONV in patients undergoing surgery for facial fracture 177 , laparoscopic surgery for suspected appendicitis 178 , and microvascular decompression surgery of the trigeminal nerve root 179 . Singh et al .…”
Section: Perioperative Antiemetic Drugs Used For the Treatment And/ormentioning
confidence: 99%